Levamisole in Medicine - Fnu Nutan (Internal Medicine, 2018)
Levamisole is a common antihelminth used in veterinary medicine. It caught the attention of the medical community in 2008 when it was discovered to be the cause of agranulocytosis in people using illicit substances contaminated with levamisole. Subsequently multiple other deleterious effects have been recorded with the use of cocaine laced with this drug as discussed below.1 Prior to the widespread use of levamisole in cocaine, it was shown to cause the same deleterious effect in the pediatric population in whom it was used in chemotherapy regimen.